2013
DOI: 10.1071/am12047
|View full text |Cite
|
Sign up to set email alerts
|

An inland population of the common ringtail possum (Pseudocheirus peregrinus) at Black Rock Ridge, New South Wales: a preliminary ecological assessment

Abstract: The common ringtail possum (Pseudocheirus peregrinus) is considered abundant throughout its distribution in eastern Australia but appears to be declining at a regional level in inland New South Wales. Previous studies of the common ringtail possum in south-eastern Australia have focussed on coastal populations and little is known about the ecology of inland populations. In south-western Australia studies of the closely related western ringtail possum (Pseudocherius occidentalis) have found that coastal populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In this study, we did not observe any dreys and there was no bamboo suitable for building nests. Field observations have however suggested that D. gliroides nests in tree hollows (Franco et al 2011) similar to Australasian marsupials (Geiser 1994;Kerle et al 2013), and that they use introduced nest boxes (Franco et al 2011;Celis-Diez et al 2012). A lack of mature trees with hollows in the PNLA would therefore reduce potential nesting sites for D. gliroides and hence reduce the habitat available to them.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we did not observe any dreys and there was no bamboo suitable for building nests. Field observations have however suggested that D. gliroides nests in tree hollows (Franco et al 2011) similar to Australasian marsupials (Geiser 1994;Kerle et al 2013), and that they use introduced nest boxes (Franco et al 2011;Celis-Diez et al 2012). A lack of mature trees with hollows in the PNLA would therefore reduce potential nesting sites for D. gliroides and hence reduce the habitat available to them.…”
Section: Discussionmentioning
confidence: 99%